1996
DOI: 10.1073/pnas.93.22.12267
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of human fetal globin expression is impaired in the absence of the adult beta-globin gene activator protein EKLF.

Abstract: Globin genes are subject to tissue-specific and developmental stage-specific regulation. A switch from human fetal ('y)-to adult (,B)-globin expression occurs within erythroid precursor cells of the adult lineage. Previously we and others showed by targeted gene disruption that the zinc finger gene, erythroid Kruippel-like factor (EKLF), is required for expression of the f3-globin gene in mice, presumably through interaction with a high-affinity binding site in the proximal promoter. To examine the role of EKL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
133
1
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(141 citation statements)
references
References 36 publications
5
133
1
2
Order By: Relevance
“…EKLF knockout mice die of severe anemia at the fetal liver stage, due to failure of adult β-globin gene activation. EKLF Ϫ/Ϫ mice bearing a complete human β-globin locus transgene have reduced levels of β-globin but elevated levels of γ-globin expression, compared with wild-type mice bearing the same transgene [41,42]. Our RT-PCR experiments showed that EKLF is expressed in K562 cells, but no significant difference in EKLF expression was found between cells transfected with non-siRNA and siRNA against BP1.…”
Section: Discussionmentioning
confidence: 60%
“…EKLF knockout mice die of severe anemia at the fetal liver stage, due to failure of adult β-globin gene activation. EKLF Ϫ/Ϫ mice bearing a complete human β-globin locus transgene have reduced levels of β-globin but elevated levels of γ-globin expression, compared with wild-type mice bearing the same transgene [41,42]. Our RT-PCR experiments showed that EKLF is expressed in K562 cells, but no significant difference in EKLF expression was found between cells transfected with non-siRNA and siRNA against BP1.…”
Section: Discussionmentioning
confidence: 60%
“…Deletion of 5ЈHS3 in the endogenous mouse locus results in a 30% reduction of ␤ gene expression in adult mice (Hug et al 1996). Natural mutations in the CACC box of the ␤-globin promoter result in a less severe reduction of ␤ gene expression than observed in EKLF knockout mice (Thein 1993;Perkins et al 1996;Wijgerde et al 1996). Thus, it appears that EKLF sites are necessary in both the promoter and the LCR and that these sites act independently of each other.…”
Section: Eklf and Activation Of The ␤-Globin Locusmentioning
confidence: 99%
“…EKLF mRNA is highly restricted in its expression pattern, limited to hematopoietic organs such as the yolk sac, fetal liver, adult bone marrow, and the red pulp of the spleen [8,9]. Molecular and genetic ablation studies demonstrate that EKLF is absolutely required for β-globin transcription and plays a prominent role in the final developmental switch to adult β-globin in definitive erythroid cells [10][11][12][13][14]. EKLF protein can interact with coactivators such as p300/CBP histone acetyltransferases as well as chromatin remodelers such as SWI/SNF to maximally transactivate the β-globin gene [15,16].…”
Section: Introductionmentioning
confidence: 99%